Analisis Faktor-Faktor Yang Mempengaruhi Implementasi Kebijakan Pantas Sehat Pada Pegawai Puskesmas Kabupaten Kutai Kartanegara (Peraturan Bupati Kutai Kartanegara No. 66 Tahun 2019 Tentang Penyelenggaraan Gerakan Keluarga Peduli Pencegahan Dan Atasi Stun - Imanuddin, Khairul; Adrianto, Ratno; Annisa Nurracmawati (Syntax Corporation, 2025)
Stunting as a condition of growth failure caused by lack of nutrition in the first 1000 days of life. The prevalence of stunting in toddlers in Kutai Kartanegara Regency in 2021 was 26% and increased in 2022 by 27.1% with a target of 21.89%, so the target is still achievable. Efforts to prevent stunting in Kutai Kartanegara Regency through the Pantas Sehat program policy. Observations of the stunting prevention program still lack socialization and there are errors in receiving information in implementing the policy, lack of understanding of staff at the locus, the division of authority has not been running well and some facilities are inadequate. For this reason, it is necessary to look at the implementation of the program through communication, resources, disposition and bureaucratic structure. The aim of this research was to analyze factors that influence implementation health care policies among Community Health Center employees in Kutai Kartanegara Regency. Cross Sectional method study design. The sample was employees at Community Health Center in Kutai Kartanegara Regency, totaling 160 people. The sampling technique used was purposive sampling. Bivariate data analysis used was chi square and multivariate used was logistic regression. The results study indicate that communication, resources, and bureaucratic structure have a significant effect on the implementation Pantas Sehat policy, while disposition does not have a significant effect on the implementation Pantas Sehat policy. The logistic regression equation model is Implementation = 4.467 + 1.628 (Communication) + 0.522 (Resources) + 0.264 (Disposition) + 1.482 (Bureaucratic Structure) + e. R Square of 0.338 means the level of influence of communication, resources, disposition and bureaucratic structure on the implementation Pantas Sehat policies for Puskesmas employees in Kutai Kartanegara Regency is 33.8%. It was concluded that the factors that influence the implementation Pantas Sehat policy include communication, resources, disposition and bureaucratic structure. Communication variable was the most dominant. It was recommended to improve communication through counseling and socialization to mothers who have under five years children regarding exclusive breastfeeding and routine immunizations carried out every month using interesting and diverse media.